A vector–host epidemic model with spatial structure and age of infection. (June 2018) - Fitzgibbon, W.E.; Morgan, J.J.; Webb, Glenn F.; Wu, Yixiang
Abstract: In this paper we study a diffusive age structured epidemic model with disease transmission between vector and host populations. The dynamics of the populations are described by reaction–diffusion equations, with infection age structure of the host population incorporated to account for incubation periods. The disease is transmitted between vector and host populations in crisscross fashion. The existence of solutions of the model is studied by operator semigroup methods, and the asymptotic behavior of the solution is investigated.